The Posture Triangle A New Framework for U.S. Air Force Global Presence - Pettyjohn, Stacie L. (Research Reports, 2013)
U.S. Air Force (USAF) global posture-its overseas forces, facilities, and arrangements with partner nations-faces a variety of fiscal, political, and military challenges. This report seeks to identify why the USAF needs a global posture, where it needs basing and access, the types of security partnerships that minimize peacetime access risk, and the amount of forward presence that the USAF requires.